비대면 국회 도입을 위한 방안 모색 - 이정진 (의정논총, 15(2), 2020)
본 논문은 코로나19 확산이라는 국가적 재난상황에서 국회의 지속성을 유지하기 위해비대면 국회를 도입하기 위한 방안을 모색하는 것을 목적으로 한다. 현행 국회법은 국회에서의 회의와 표결을 위해 국회의원의 출석을 전제로 하고 있기 때문에 비대면 국회 운영을위해서는 국회법 개정이 필요하다. 또한 비대면 국회 도입과 관련하여 비대면 회의의 요건, 회의 방식, 적용 범위 등에 대한 논의가 선행되어야 할 것이다. 미국에서는 이미 9.11 테러 이후 국가적 위기 상황에서 연방의회의 입법기능을 유지하기위한 비대면 의회 운영이 논의되어 왔으며. 코로나19 확산으로 인해 한시적으로 비대면 의회를 운영하고 있다. 영국 하원에서도 한시적으로 비대면 회의와 표결을 도입하는 등 각국의회는 각자의 정치 문화와 기술 수준에 맞추어 다양한 방식으로 비대면 의회를 운영하고있다. 우리 국회는 일찍이 전자투표 시스템을 도입한 전자의회 선진국으로 비대면 국회 운영을 위한 적절한 환경을 가지고 있다. 또한 감염병의 확산 뿐 아니라 자연재해나 테러 등국가적 위기상황에서 국회의 입법과 의정활동이 더욱 중요하다는 점에서 관련 법률 개정등 비대면 국회 도입을 위한 논의와 대응 방안 마련이 시급하다. This paper investigates the remote voting in the Parliaments and argue that discussions are needed to introduce a virtual parliament in the national disaster situation of the spread of Covid-19. Since the current National Assembly Act presupposes lawmakers to attend meetings and votes at the National Assembly, a revision of the National Assembly Act is necessary to operate the Virtual Parliament. In the United States, the operation of remote voting at parliaments has already been discussed to maintain the legislative function in the face of a national crisis since the September 11 attacks. Due to the spread of Covid-19, it has temporarily operated remote voting. The House of Commons also temporarily introduces remote meetings and votes, and each country's parliament operates non-face-to-face meetings in various ways according to their respective political culture and technology levels. National Assembly of the Republic of Korea is an advanced country in the former council that introduced the electronic voting system earlier, and has a proper environment for non-face-to-face parliamentary operations. In addition, it is urgent to discuss and prepare countermeasures for the introduction of non-face-to-face National Assembly, including revision of related laws, as legislative and parliamentary activities are more important in national crises such as natural disasters and terrorism as well as the spread of infectious diseases. KCI Citation Count: 0